Effects of Testosterone and Levonorgestrel Combined with a 5α-Reductase Inhibitor or Gonadotropin-Releasing Hormone Antagonist on Spermatogenesis and Intratesticular Steroid Levels in Normal Men - Matthiesson, Kati L.; Stanton, Peter G.; O’Donnell, Liza; Meachem, Sarah J.; Amory, John K.; Berger, Richard; Bremner, William J.; McLachlan, Robert I. (The journal of clinical endocrinology and metabolism, 2005)
Context: Combination of a GnRH antagonist (acyline), types I and II, 5α-reductase inhibitor (dutasteride) or levonorgestrel (LNG) with testosterone (T) treatment may augment the suppression of spermatogenesis and intratesticular (iT) steroids. Objective: The objective of this study was to assess the effects of combined hormonal contraceptive regimens on germ cell populations and iT steroids. Design, Setting, and Participants: Twenty-nine normal health men enrolled in this prospective, randomized, 14-wk study at the University of Washington. Intervention(s): Twenty-two men (n = 5–6/group) received 8 wk of T enanthate (TE; 100 mg, im, weekly) combined with 1) 125 μg LNG daily, orally; 2) 125 μg LNG plus 0.5 mg dutasteride daily, orally; 3) 300 μg/kg acyline twice weekly, sc; or 4) 125 μg LNG daily, orally, plus 300 μg/kg acyline twice weekly, sc. Subjects then underwent a vasectomy and testicular biopsy. Control men (n = 7) proceeded directly to surgery. Main Outcome Measure(s): The main outcome measures were germ cells and iT steroids [T, dihydrotestosterone, 3α- and β-androstanediol (Adiol), and estradiol (E2)]. Results: High iT levels of all androgens (6- to 123-fold serum levels) and E2 (407-fold serum levels) were found in control men. iTT (1.9–2.6% control; P < 0.001) and iT3βAdiol (16–34% control; P < 0.05) levels decreased with all treatments. iT dihydrotestosterone (13–29% control; P < 0.05) and iT3αAdiol (44–47% control; P < 0.05) levels decreased with all but the TE plus LNG treatment. iTE2 levels decreased only in the TE plus acyline group (28% control; P = 0.01). Germ cells from type B spermatogonia onward were suppressed, with no differences between groups found. Variable sites of impairment of germ cell progression were evident between men (spermagonial maturation, meiosis 1 entry, and spermiation). Other than a negative correlation between iT3αAdiol and haploid germ cell number (P < 0.006), no correlations between germ cell number and gonadotropins, sperm concentration, or iT steroids were found. Conclusions: A similar high testicular:serum gradient exists for E2 and T in normal men, and 8 wk of gonadotropin suppression markedly reduces iTT, with 5α-reduced androgens and E2 levels decreasing to a much lesser degree. The heterogeneity of the germ cell response, regardless of treatment, gonadotropins or iT steroids, points to the individual sensitivity of sites in germ cell development, which is worthy of additional exploration.